Microstructure and dielectric properties of La1-x(Ba,Ca)x Mn0.40Ti0.60O3 (0.30 ≤ x ≤ 0.50) ceramic systems - Sinin, Aaliyawani Ezzerin (2015)
Composites of La1-xAxMn0.40Ti0.60O3 with A = Ba and Ca where 0.30 ≤ x ≤ 0.50 were prepared by the conventional solid-state reaction method. The samples were calcined twice at 800 °C for 12 hours and 1000 °C for 12 hours in powder form. Powder samples were pressed into pellets and sintered at 1200 °C for 12 hours. The sintered composites were characterized in terms of microstructure, crystal structure and dielectric properties at frequency range of 0.01 Hz – 100 kHz at room temperature to 200 °C using the scanning electron microscope (SEM), the X-ray diffraction method (XRD), and a low frequency LCR analyzer respectively. The surface morphology of the samples shows rod-like and rounded grains for both series of samples. La1-xBaxMn0.40Ti0.60O3 has rounded grains with diameter approximately 1.675 μm and rod-like grains with length approximately 5.280 μm. For La1-xCaxMn0.40Ti0.60O3, the spherical shaped grains are 0.558 μm in diameter and rodlike grains with length of 1.083 μm. XRD analysis shows that both La1- xBaxMn0.4Ti0.6O3 and La1-xCaxMn0.4Ti0.6O3 have cubic, Pm3m structure with a few impurity peaks. Increasing the amount of barium and calcium ions at lanthanum site has increased the lattice parameter from 3.9404 Ǻ to 3.9553 Ǻ and volume ranging from 61.18 Ǻ3 to 61.88 Ǻ3 for La1-xBaxMn0.40Ti0.60O3 and from 3.9370 Ǻ to 3.9579 Ǻ for lattice parameter and volume, from 61.02 Ǻ3 to 62.00 Ǻ3 for La1-xCaxMn0.40Ti0.60O3 samples. Dielectric properties measurement shows that the dielectric permittivity depends strongly on the applied frequency and temperature. The real part of dielectric permittivity, εʹ increases with the decreasing frequency and increases with the increasing temperature due to space-charge polarization and thermally activated electron hopping. A graph of log permittivity, εʹ versus temperature, T (K) was plot at 1 Hz, 1 kHz, and 10 kHz showing that the dielectric permittivity is more stable at all temperatures at higher frequencies that are 1 kHz and 10 kHz which is in the range of 1000 to 10000 for all samples. At 1 Hz, the dielectric permittivity for both barium and calcium series increase slightly from 100000 to 1000000 as the sample is heated. Analysis on the real part of capacitance, Cʹ and imaginary capacitance, Cʹʹ data under the function of frequency using the universal capacitor response reveal that the samples are dominated by diffusion in series with a quasi d.c process at room temperature and a quasi d.c process from a temperature of 313.15 K and above for La1-xBaxMn0.40Ti0.60O3. For La1-xCaxMn0.40Ti0.60O3, only quasi d. c. process takes place for all temperatures. The characteristic frequency, fc is found to be temperature dependence, the value of the fractional correlation, p is close to 1 indicates that the electrons motion are highly correlated at intercluster region while the correlation coefficients for specific intracluster, n decreases as temperature increases. The activation energy for both series has a value ranging from 0.30 eV to 0.50 eV for La1-xBaxMn0.40Ti0.60O3 and from 0.10 eV to 0.20 eV for La1-xCaxMn0.40Ti0.60O3.